Eksistensi Kebudayaan Kampung Adat Banceuy sebagai Warisan Nenek Moyang dalam Melestarikan Budaya Lokal Desa Sanca Kecamatan Ciater Kabupaten Subang - Neneng Tri Puspita; Lili Halimah; Moh Isman Al Latif (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2024)
Banceuy Traditional Village, located in Sanca Village, Ciater District, Subang Regency, West Java, is one of the traditional villages rich in cultural values ​​and traditions. This study aims to explore how the preservation of culture and local wisdom in Banceuy Traditional Village can affect the socio-economic development of the community. With a qualitative approach and field research methods, data were collected through interviews with traditional leaders, local communities, and observations of traditional and artistic activities. The results of the study indicate that the preservation of culture and local wisdom has a positive impact on improving the economy, especially through the culture-based tourism sector and sustainable natural resource management. This study also emphasizes the importance of traditional education in ensuring cultural sustainability among the younger generation.